Michael Dummett: antirealism and the existence of God - Arango, Pablo R. (Discusiones Filosóficas, 2013)
This paper expounds the views of Michael Dummett about the debates between realists and anti-realists in metaphysics, emphasizing the general shape of the anti-realist argument. Lastly, the commitment that, according to Dummett, should adopt the anti-realist with respect to the existence of God is showed.